2020
DOI: 10.1002/2211-5463.12934
|View full text |Cite
|
Sign up to set email alerts
|

Novel immune subtypes of lung adenocarcinoma identified through bioinformatic analysis

Abstract: The magnitude of the immune response is closely associated with clinical outcome in patients with cancer. However, finding potential therapeutic targets for lung cancer in the immune system remains challenging. Here, we constructed a vital immune‐prognosis genes (VIPGs) based cluster of lung adenocarcinoma (LUAD) from IMMPORT databases and The Cancer Genome Atlas. A transcription factor regulatory network for the VIPGs was also established. The tumor microenvironment of LUAD was analyzed using the ESTIMATE (Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Current studies have found that the development of cancer are not only dependent on tumor cell characteristics but are also affected by the interaction with infiltrated immunocytes [ 30 , 31 ]. The tumors with higher immune cells and mediators proportion were proved to be more effective to the immune treatment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have found that the development of cancer are not only dependent on tumor cell characteristics but are also affected by the interaction with infiltrated immunocytes [ 30 , 31 ]. The tumors with higher immune cells and mediators proportion were proved to be more effective to the immune treatment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For breast cancer, Zheng et al developed an immune phenotype classifier for predicting both immune activity within the tumor microenvironment and prognoses for patients with triple-negative breast cancer [24]. In addition, numerous investigations have been conducted using immune subtypes to predict clinical prognoses and treatment guidance for bladder cancer [25], ovarian carcinoma [26], uveal melanoma [27], lung cancer [28,29], and head and neck cancers [30]. Here, we have identified two immune system-related PC phenotypes with differing transcription level scores among immune-cell subsets using a CIBERSORT analysis and further characterized their differences using a multiomic approach.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study used immunogenomic profiling of 29 immune signatures to identify three distinct LUAD subtypes (Immunity High, Immunity Medium, and Immunity Low) 15 . Similarly, Qin et al utilized critical immune-prognosis genes for patients with LUAD and stratified the patients into low-immunity and high-immunity subtypes 16 . In another study, researchers performed consensus clustering on differentially expressed aging-related genes in the Cancer Genome Atlas (TCGA) database.…”
Section: Introductionmentioning
confidence: 99%